Adaptability-oriented hierarchical correlation optimisation in product family design. (2017) - Cheng, Xianfu; Luo, Junyi; Gao, Dongshan
For leader-follower characteristic between platform parameters and customisation parameters in product family design, a bi-level model and leaderfollower correlation optimisation model are developed. The adaptability of platform parameters is considered, and they are regarded as association parameters to transfer between the upper and lower in the model. After the values of platform variables in the upper level model are assigned, each sub-plan problem in the lower level model can be solved without relying on platform parameters under certain conditions. Simultaneously, incidence relation of platform parameters could be taken as relaxation constraints, and genetic algorithm is applied to solve the leader-follower correlation optimisation model of the product family. Finally, an example on optimal design of product family for drum group is used to demonstrate the feasibility of the established model and proposed method.